2011
DOI: 10.1039/c1ce05410d
|View full text |Cite
|
Sign up to set email alerts
|

Direct production of carbamazepine–saccharin cocrystals from water/ethanol solvent mixtures by membrane-based crystallization technology

Abstract: This communication reports on the possibility to achieve the direct production of either carbamazepine crystals or carbamazepinesaccharin cocrystals from water/ethanol solvent mixtures by using membrane-based crystallization technology, by choosing the opportune initial conditions.Co-crystallization of active pharmaceutical ingredients (APIs) with cocrystal formers 1 (or conformers) has become increasingly important in the last few years in the drug-development process, primarily because it provides an alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…By controlling the crystallization parameters, it was shown that one could eliminate nucleation of an undesirable metastable crystal form and produce large particles with a minimum content of fines. The use of membrane-based crystallization technology has been investigated for the production of cocrystals of carbamazepine and saccharin . In this approach, as long as the initial composition of the aqueous ethanol solvent system was optimized, the membrane technology enabled one to control the degree of supersaturation during the process and thus obtain the desired product.…”
Section: Preparation Of Cocrystal Systems and Methodologies For Chara...mentioning
confidence: 99%
See 1 more Smart Citation
“…By controlling the crystallization parameters, it was shown that one could eliminate nucleation of an undesirable metastable crystal form and produce large particles with a minimum content of fines. The use of membrane-based crystallization technology has been investigated for the production of cocrystals of carbamazepine and saccharin . In this approach, as long as the initial composition of the aqueous ethanol solvent system was optimized, the membrane technology enabled one to control the degree of supersaturation during the process and thus obtain the desired product.…”
Section: Preparation Of Cocrystal Systems and Methodologies For Chara...mentioning
confidence: 99%
“…The use of membrane-based crystallization technology has been investigated for the production of cocrystals of carbamazepine and saccharin. 35 In this approach, as long as the initial composition of the aqueous ethanol solvent system was optimized, the membrane technology enabled one to control the degree of supersaturation during the process and thus obtain the desired product.…”
Section: Crystal Growth and Designmentioning
confidence: 99%
“…A more challenging case is constituted by polycrystalline mixtures such as those composed of polymorph III of carbamazepine (CBZ III), saccharin (SAC), and their co-crystal form (CBZ-SAC), which are typically produced by crystallization processes aiming at obtaining co-crystals from an active pharmaceutical ingredient and a co-former (Di Profio et al, 2011). This mixture was analysed by XRPD and FT-IR spectroscopy, and the corresponding measured profiles after application of pre-processing are plotted in Fig.…”
Section: Ternary Carbamazepine-saccharin Mixtures Studied By Powder Xmentioning
confidence: 99%
“…Solvent mixtures can reduce the solubility differences between cocrystal components; facilitate nucleation rate and provide improved transformation kinetics for cocrystallization [ 22 , 23 , 24 ]. Di Profio has successfully prepared carbamazepine-saccharin cocrystal in water/ethanol solvent mixtures by membrane-based crystallization technology [ 25 ]. In this study, ethanol-water solvent mixture was also applied to try to prepare CBZ cocrystal through a combination of solution evaporation and the cooling crystallization method.…”
Section: Introductionmentioning
confidence: 99%